ADHD WITH NON-ORGANIC ENURESIS AND BORDERLINE INTELLIGENT QUOTIENT - Frilya Rachma Putri; Herman Yosef (Journal of Psychiatry Psychology and Behavioral Research, 2021)
Symptoms of Attention Deficit Hyperacitivity Disorder (ADHD) can be associated with nocturnal enuresis. Nocturnal enuresis cases are common occur in children with Mental Retardation. There are several hypotheses underlying this comorbidity, such as genetic, neurophysiological, environmental and psychosocial factors. We report the case of a 7 year old boy with symptoms such as inability to concentrate, active movement, talk a lot, unable to wait his turn, unable to delay desires, easy fighting and behaving and speaking harshly. Patients still wet the bed at night at least 3-4 times a week The Abbreviated Conners Score rating scale assessed by the mother at the start of treatment was 21. The IQ test score was 71 and the Strength and Difficulty Questionnaire (SDQ) score was 35. The patient's symptoms were reduced after 4-month therapy with 2x5mg of methylphenidate administration, psychoeducation of parents to implement toilet training and behavior therapy for patients, apply reward and punishment with the principle of token economy. In the development process of children and adolescents, parenting is an important factor. Many studies shows that parenting can impact the resilience and vulnerability of a child to behavioral disorders. In children with ADHD with borderline IQ and enuresis, parenting with a high parental control component can cause psychological symptoms to worsen without being balanced with the attitude of parents who are responsive to the psychological needs of the child.